Islet‐derived damage‐associated molecular pattern molecule contributes to immune responses following microencapsulated neonatal porcine islet xenotransplantation in mice. (15th July 2016) - Itoh, Takeshi; Hata, Yuko; Nishinakamura, Hitomi; Kumano, Kenjiro; Takahashi, Hiroyuki; Kodama, Shohta
Abstract: Background: Clinical allogeneic islet transplantation has become an attractive procedure for type 1 diabetes mellitus treatment. However, there is a severe shortage of human donors. Microencapsulated neonatal porcine islet (NPI) xenotransplantation may be an alternative transplantation procedure. Currently, the efficacy of microencapsulated NPI xenotransplantation into the peritoneal cavity is limited because of early non‐function resulting from inflammation, which is a serious hindrance to promoting this procedure as a standard therapy. Previously, we have demonstrated that high‐mobility group box 1 (HMGB1), a damage‐associated molecular pattern (DAMP) molecule, was released from transplanted islets and triggered inflammatory reactions leading to early loss of intrahepatic syngeneic islet grafts in mice. In this study, we hypothesized that the inflammatory reaction in the peritoneal cavity following the transplantation of microencapsulated NPIs is more severe than that of empty capsules. Additionally, we predicted that HMGB1 released from transplanted microencapsulated NPIs triggers further inflammatory reactions in mice. Finally, we hypothesized that microencapsulated NPI xenotransplantation efficacy would be improved by treatment‐targeting inflammatory reactions in a mouse model. Methods: A total of 10 000 empty capsules (alginate–poly‐L‐ornithine–alginate) or 10 000 IEQ microencapsulated NPIs were transplanted into the peritoneal cavity of streptozotocin‐induced diabetic C57BL/6 mice. Results: The numbers of mononuclear cells in the peritoneal cavity following empty capsule or microencapsulated NPI transplantation were 4.8 × 10 6  ± 0.9 × 10 6 and 13.6 × 10 6  ± 3.0 × 10 6, respectively (P < 0.05). Fluorescence‐activated cell sorting (FACS) analysis revealed that tumor necrosis factor (TNF)‐α‐, interleukin (IL)‐6‐, interferon (IFN)‐γ‐, and/or IL‐12‐positive macrophages, neutrophils, and dendritic cells had infiltrated the peritoneal cavity after empty capsules or microencapsulated NPIs administration. IL‐6 concentrations in the peritoneal lavage fluids on 7 days after empty capsule or microencapsulated NPI transplantation were 18.5 ± 10.0 and 157.4 ± 46.3 pg/ml, respectively (P < 0.001), while TNF‐α concentrations were 4.6 ± 1.4 and 19.8 ± 8.4 pg/ml, respectively (P < 0.01). In addition, HMGB1 concentrations were 37.6 ± 6.6 and 117.4 ± 8.1 ng/ml, respectively (P < 0.0001). In vitro experiments revealed that the total amount of released HMGB1 into the culture medium of empty capsule (200 capsules/dish) and microencapsulated NPI (200 IEQ/dish) after hypoxic culture (1% O2, 5% CO2, and 94% N2 ) was 0 and 8.6 ± 2.2 ng, respectively (P < 0.001). FACS analysis revealed that TNF‐α‐ and IL‐6‐positive macrophages were also observed in the peritoneal cavity following intraperitoneal injection of HMGB1 itself. Anti‐TNF‐α antibody treatment was associated with slightly prolonged graft survival and improved glucose tolerance 30 days after transplantation, but none of the recipients were remained normoglycemic. Conclusions: In conclusion, early inflammatory reactions might be therapeutic targets for the prolongation of microencapsulated NPIs graft survival. Thus, treatment‐targeting inflammation might improve the efficiency of clinical microencapsulated NPI xenotransplantation.